2015
DOI: 10.1080/19381956.2015.1107253
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to noninherited maternal antigens, reproductive microchimerism and regulatory T cell memory: 60 years after ‘Evidence for actively acquired tolerance to Rh antigens’

Abstract: Compulsory exposure to genetically foreign maternal tissue imprints in offspring sustained tolerance to noninherited maternal antigens (NIMA). Immunological tolerance to NIMA was first described by Dr. Ray D. Owen for women genetically negative for erythrocyte rhesus (Rh) antigen with reduced sensitization from developmental Rh exposure by their mothers. Extending this analysis to HLA haplotypes has uncovered the exciting potential for therapeutically exploiting NIMA-specific tolerance naturally engrained in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 105 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…The effect is less robustly sustained in between pregnancies, and the overall differential predilection toward tolerance is attributed to molecular and functional differences between fetal and adult T cells, with fetal T cells having greater predisposition toward Treg formation . While maternal Treg with specificity to fetal cells transmitted to the mother may have a role, their impact on tolerance after solid organ transplantation is not known …”
Section: Potential Impact Of Maternal‐fetal Microchimerismmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect is less robustly sustained in between pregnancies, and the overall differential predilection toward tolerance is attributed to molecular and functional differences between fetal and adult T cells, with fetal T cells having greater predisposition toward Treg formation . While maternal Treg with specificity to fetal cells transmitted to the mother may have a role, their impact on tolerance after solid organ transplantation is not known …”
Section: Potential Impact Of Maternal‐fetal Microchimerismmentioning
confidence: 99%
“…46 While maternal Treg with specificity to fetal cells transmitted to the mother may have a role, their impact on tolerance after solid organ transplantation is not known. 47 Several studies have established that maternal origin cells are present at a higher proportion in the livers of infants with BA when compared to non-BA controls. 39,[48][49][50][51] Muraji et al identified that these maternal origin cells included CD8 + T cells, CD45 + lymphocytes, and cytokeratin-positive biliary epithelial cells, all in proximity to portal triads with evidence of inflammatory degeneration.…”
Section: P Otential Impac T Of Maternal-fe Tal Microchimeris Mmentioning
confidence: 99%
“…Priming the expansion of maternal T reg cell populations, and other suppressive adaptive immune components, with specificity that averts maternal–fetal conflict during pregnancy 2527,35,128 …”
Section: Figmentioning
confidence: 99%
“…This article does for microchimerism what the 1945 Science paper did for mixed chimerism. [Note: the authors recently elaborated on direct relationship of their work to the 1954 PNAS article in a special issue of Chimerism devoted to Owen's legacy .] What they discovered is that microchimerism derived from the mother is necessary and sufficient to sustain a regulatory type of tolerance into adult life.…”
mentioning
confidence: 99%
“…The pTregs are distinguishable from tTregs by their low expression of the zinc‐finger nucleoprotein Helios. The article's principal claims are that that maternal cells transmitted to the fetus confer specific tolerance to the NIMAs; tolerance is maintained by Helios low FoxP3 + pTregs; daughters are particularly affected due to the presence of high levels of intrauterine microchimerism; the maintenance of tolerance, exemplified by protection from fetal wastage, and the pTregs that mediate it, requires the persistence of maternal microchimerism in the daughter mouse, and microchimerism‐mediated protection from fetal wastage requires mate selection in which the NIMAs will be expressed by the daughter mouse's fetus (see Figure for a summary of the main features of the study).…”
mentioning
confidence: 99%